Research on Male Adolescent School Dropout and Its Influence on Society Aged between 14 and 18 Years (International Journal of Scientific Research and Management (IJSRM), 2016)
Even though school completion rates have continually grown during much of past 100 years, dropping out of school persists as a problem that interferes with educational system efficiency and the most straightforward and satisfying route to individual educational goals for young people. Young people drop out of school for various reasons, necessities, or disillusionment with the system from which the individual in question leaves. This is according to Bill and Melinda (2013)